Nuclear ANLN regulates transcription initiation related Pol II clustering and target gene expression - Yu-Fei Cao; Hui Wang; Yong Sun; Bei-Bei Tong; Wen-Qi Shi; Liu Peng; Yi-Meng Zhang; Yu-Qiu Wu; Teng Fu; Hua-Yan Zou; Kai Zhang; Li-Yan Xu; et al. (Nature Communications)
Abstract Anillin (ANLN), a mitotic protein that regulates contractile ring assembly, has been reported as an oncoprotein. However, the function of ANLN in cancer cells, especially in the nucleus, has not been fully understood. Here, we report a role of nuclear ANLN in gene transcriptional regulation. We find that nuclear ANLN directly interacts with the RNA polymerase II (Pol II) large subunit to form transcriptional condensates. ANLN enhances initiated Pol II clustering and promotes Pol II CTD phase separation. Short-term depletion of ANLN alters the chromatin binding and enhancer-mediated transcriptional activity of Pol II. The target genes of ANLN-Pol II axis are involved in oxidoreductase activity, Wnt signaling and cell differentiation. THZ1, a super-enhancer inhibitor, specifically inhibits ANLN-Pol II clustering, target gene expression and esophageal squamous cell carcinoma (ESCC) cell proliferation. Our results reveal the function of nuclear ANLN in transcriptional regulation, providing a theoretical basis for ESCC treatment.